Association between coffee intake and frailty among older American adults: A population-based cross-sectional study - Pang, Shuo; Miao, Guangrui; Zhou, Yuanhang; Duan, Mingxuan; Bai, Linpeng; Zhao, Xiaoyan (Frontiers in Nutrition, 2023)
Background: This study examined the association between coffee consumption and frailty in older American adults. Methods: The data of 8,157 individuals aged over 60 years from the 2007–2018 National Health and Nutrition Examination Surveys were used for this cross-sectional study. The coffee drinks were classified into two categories: caffeinated and decaffeinated. Frailty was measured using the 53-item frailty index. Weighted binary logistic regression was used to evaluate the association between coffee intake and frailty risk. Restricted cubic spline models were used to assess the dose-response relationship between coffee intake and frailty. Results: Of the 8,157 participants, 2,502 (29.4%) had frailty. Compared with those who reported no coffee consumption, the odd ratios (ORs) (95% confidence intervals [CIs]) of total coffee consumption > 496 (g/day) were 0.61(0.50,0.74) in the fully adjusted model. Compared with those who reported no caffeinated coffee consumption, the ORs (95% CIs) of total coffee consumption > 488.4 (g/day) were 0.67 [0.56,0.80]) in the fully adjusted model. Compared with those who reported no decaffeinated coffee consumption, the ORs (95% CIs) of total coffee consumption > 0 (g/day) were 0.85 (0.70,1.04) in the fully adjusted model. Nonlinear associations were detected between total coffee and caffeinated coffee consumption and frailty. In the subgroup analyses by smoking status, the association between coffee consumption and the risk of frailty was more pronounced in non-smokers (P < 0.05 for interaction). Conclusion: Caffeinated coffee consumption was independently and nonlinearly associated with frailty, especially in nonsmokers. However, decaffeinated coffee consumption was not associated with frailty.